2020
DOI: 10.1038/s41598-020-77561-6
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant alpha-1-microglobulin (A1M) knockout mice exhibit features of kidney and placental damage, hemodynamic changes and intrauterine growth restriction

Abstract: Alpha-1-microglobulin (A1M) is an antioxidant previously shown to be elevated in maternal blood during pregnancies complicated by preeclampsia and suggested to be important in the endogenous defense against oxidative stress. A knockout mouse model of A1M (A1Mko) was used in the present study to assess the importance of A1M during pregnancy in relation to the kidney, heart and placenta function. Systolic blood pressure (SBP) and heart rate (HR) were determined before and throughout gestation. The morphology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…It is reported that fetal alveolar neutrophils can be activated and then reactive oxygen species (ROS) are released when maternal intrauterine infection occurs [ 10 ]. Of note, ROS-induced breaking of DNA strands results in activation of polyadenosine diphosphate ribose polymerase-1 (PARP-1), and excessive activation of PARP-1 causes cell death [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that fetal alveolar neutrophils can be activated and then reactive oxygen species (ROS) are released when maternal intrauterine infection occurs [ 10 ]. Of note, ROS-induced breaking of DNA strands results in activation of polyadenosine diphosphate ribose polymerase-1 (PARP-1), and excessive activation of PARP-1 causes cell death [ 11 ].…”
Section: Introductionmentioning
confidence: 99%